Unplanned pregnancy among married women: an exploratory study in a rural area of Bengal - Pal, Manika; Bandyopadhyay, Lina; Dasgupta, Aparajita (International Journal Of Community Medicine And Public Health, 2017)
Background: Globally unplanned pregnancy has emerged as a major public health problem with its impact on demography and economy. Despite being the first country to initiate a nationwide family planning program, contraceptives access and utilization are low in India. As per a study conducted in 35 low- and middle-income countries, India contributed the largest number of undesired pregnancy. Our current study was aimed at determining the proportion of unplanned pregnancy and examining its predictors among currently married women aged 15-35 years, residing in a rural area. Methods: A facility based, observational, cross-sectional study was conducted in a rural area of Bengal. 158 participants were selected by purposive sampling and face to face interviews were conducted using structured schedule ensuring confidentiality. Statistically data were summarized with descriptive statistics and adjusted with binary logistic regression analysis in SPSS (version 16). Results: The proportion of unplanned pregnancy was found to be 28.5%. On multivariable logistic regression, it was observed that there was significant association between unplanned pregnancy and low SE status AOR (CI) 2.523 (1.074-5.926), lack of women’s empowerment AOR (CI) 2.971 (1.198-7.367), husbands’ lower level of education AOR (CI) 2.673 (1.041-6.866), and no contraception or traditional method of contraception AOR (CI) 2.391 (1.104-5.180). Conclusions: The study revealed alarmingly high proportion of unplanned pregnancy. In addition to the existing strategies of the national program, emphasis should be on IEC activities. All efforts should be made to educate women on hazards of unsafe abortion and unplanned pregnancy.